Rice bran inclusion in the fruit and vegetable waste-based diets for fryer rabbits - S Prawirodigdo; Muryanto .; D.M Yuwono (Jurnal Ilmu Ternak dan Veteriner, 2004)
The aim of the study is to investigate the effect of rice bran inclusion in the fruit and vegetable waste (FVW)-based diets on the growth performance of fryer rabbits. Thirty-six growing rabbits (New Zealand x Flemish Giant) of about 1070.8 g initial body-weight were housed individually in the wire mesh cages and assigned to either one of a FVW-based diet containing 20% rice bran (RB 20%), 10% rice bran (RB 10%) or zero rice bran (RB 0%). Thus, each treatment consists of 12 replicates. Data were collected for 28 days. Results showed that inclusion of rice bran in the diet significantly decreased (P<0.05) dry matter intake (2888, 2830 and 3095 g, for Diets RB 20%, RB 10%, and RB 0%, respectively). Average daily weight gain of the rabbits consuming RB 20% (23 g), RB 10% (25 g) and RB 0% (33 g) was significantly different (P<0.05). Inclusion of rice bran in the FVW-based diet significantly (P<0.05) affected the feed conversion ratio of the diets (3.4 versus 4.4 and 4.1, for RB 0% versus RB 20% and RB 10%, respectively). Consistently, the average carcass weight of rabbits consuming RB 0% (1140g) was superior (P<0.05) to the carcass weight of rabbits fed RB 20% (1022 g) or RB 10% (1046 g). Overall, inclusion of rice bran in the FVW based diet is not necessary. Simultaneously, use of FVW for rabbit is promising to avoid the accumulated fermenting FVW problem and produce healthy meat instantly for food.   Key words: Fruit and vegetable waste, rice bran, fryer rabbit, growth rate, carcass